Human tooth-derived biomaterial as a graft substitute for hard tissue regeneration. (April 2017) - Rijal, Girdhari; Shin, Hong-In
Aim: The present study was conducted to evaluate the efficacy of human dentine grafts for new bone augmentation.Materials & methods: Dentine grafts (demineralized dentine matrix [DDM] and mineralized dentine matrix [MDM]) were prepared and implanted in rats. Tetracycline was administered twice. Paraffin and resin sections were prepared from the harvested grafts and stained respectively with hematoxylin and eosin (in addition to tartrate acid phosphatase for osteoclasts) and Villanueva. The new bone formation (bone thickness, mineral apposition rate and the bone formation rate) was analyzed in tetracycline-labeled resin sections.Results & conclusion: DDM grafts implanted in bone were better able to augment the bone compared to MDM grafts. However, both MDM and DDM failed to induce new bone in ectopic site, they could be considered as alternative autograft substitutes after protocol optimization.